Analogue circuit implementation of a new logistic‐like map. Issue 14 (31st May 2022) - Wu, Xianming; Fu, Longxiang; He, Shaobo; Wang, Huihai
Abstract: Discrete chaotic system has complex dynamics and becomes to be a present hot topic, but its analogue circuit implementation is rarely discussed. In this paper, by simplifying the logistic map, a new Logistic‐like map is proposed. Its cobweb plots, bifurcations, Lyapunov exponents, and dynamic map are investigated theoretically and numerically. The results show that the Logistic‐like map has complex dynamical behaviours. And then Psim simulation model is proposed to verify the feasibility of analogue circuit implementation. Finally, an analogue circuit experiment is performed and its results are consistent with the simulation results. The circuit designed is very simple and has less components, which can further broaden the applications of discrete chaotic map in applications.